Maternal mortality at the end of a decade: signs of progress? - AbouZahr Carla; Wardlaw Tessa (Bulletin of the World Health Organization, 2001)
ABSTRACT: Maternal mortality is an important measure of women?s health and indicative of the performance of health care systems. Several international conferences, most recently the Millennium Summit in 2000, have included the goal of reducing maternal mortality. However, monitoring progress towards the goal has proved to be problematic because maternal mortality is difficult to measure, especially in developing countries with weak health information and vital registration systems. This has led to interest in using alternative indicators for monitoring progress. This article examines recent trends in two indicators associated with maternal mortality: the percentage of births assisted by a skilled health care worker and rates of caesarean delivery. Globally, modest improvements in coverage of skilled care at delivery have occurred, with an average annual increase of 1.7% over the period 1989-99. Progress has been greatest in Asia, the Middle East and North Africa, with annual increases of over 2%. In sub-Saharan Africa, on the other hand, coverage has stagnated. In general, caesarean delivery rates were stable over the 1990s. Countries where rates of caesarean deliveries were the lowest - and where the needs were greatest - showed the least change. This analysis leads us to conclude that whereas there may be grounds for optimism regarding trends in maternal mortality in parts of North Africa, Latin America, Asia, and the Middle East, the situation in sub-Saharan Africa remains disquieting.